Fourier Integral Implementation to Obtain the Velocity Signal and Displacement Signal from Digital Data of MEMS Accelerometer Sensor - Wasis Wasis (Natural B, Journal of Health and Environmental Sciences, 2018)
This paper discusses and implements a simple technique to obtain the velocity and the displacement signals from the digital data of the MEMS accelerometer sensor, which is an acceleration signal. The method used is a numerical integral, i.e. discrete Fourier integral. Technically, the digital signal data from the MEMS accelerometer sensor is converted from time domain to frequency domain by using Discrete Fourier Transform (DFT). In the frequency domain, the acceleration signal component is integrated once to obtain its velocity components, and is integrated twice to obtain its displacement component. Furthermore, Invers Discrete Fourier Transform (IDFT) is performed to obtain the form of velocity and displacement signals in time domain. The application of these theories and methods gives quite good results, especially for low frequency signals recorded at high sampling rates.